(3GdEdeGe HeSGFd GdCYdGes - (3GHf MLQ GdgjJej , TgGH GdOjf CHhGdYHGS TjN GdGSdGe CMeO Hf eMeO Hf Ydj Hf MLQ GdgjKej GdSYOj GdCfUGQj,J (B974 (3g` s ((3YHO Gddg Gdeci GdQTjOi GdTGaYi s)
(3ChdgG (B:s
(3hHYO aEfi fXQJ ai cJGH GdCYdGe GdNGJeI GdeMbbjf CMeO TgGH GdOjf Hf MLQ GdgjJei GdTGaYi aEPG gh cJGH LGeY s
(3BNQgG (B:s
(3bGd ai GdCUd JhdO aJfI dge efYkG Ch GSJNaGa Ch fMhgeG Je HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3Hg ahGFO ai Chdg hBNQgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs